2018
DOI: 10.1103/physrevlett.121.235501
|View full text |Cite
|
Sign up to set email alerts
|

Depinning Dynamics of Crack Fronts

Abstract: We investigate experimentally and theoretically the dynamics of a crack front during the microinstabilities taking place in heterogeneous materials between two successive equilibrium positions. We focus specifically on the spatio-temporal evolution of the front, as it relaxes to a straight configuration, after depinning from a single obstacle of controlled strength and size. We show that this depinning dynamics is not controlled by inertia, but instead, by the rate dependency of the dissipative mechanisms taki… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 42 publications
(56 reference statements)
1
17
0
Order By: Relevance
“…The last missing ingredient is the kinetic law that relates the local crack velocity v to G and G c . For brittle materials, this kinetic law can be derived from Griffith (1921)'s criterion by accounting for the variations of the toughness with crack speed (Kolvin et al, 2015;Chopin et al, 2018). It reads :…”
Section: Kinetic Lawmentioning
confidence: 99%
See 1 more Smart Citation
“…The last missing ingredient is the kinetic law that relates the local crack velocity v to G and G c . For brittle materials, this kinetic law can be derived from Griffith (1921)'s criterion by accounting for the variations of the toughness with crack speed (Kolvin et al, 2015;Chopin et al, 2018). It reads :…”
Section: Kinetic Lawmentioning
confidence: 99%
“…is a characteristic velocity of the material tied to the rate-dependency of its toughness, and [•] + the positive part function. This equation of motion has been largely used in the literature (see for example (Gao and Rice, 1989;Ramanathan et al, 1997;Ponson and Bonamy, 2010)) and was recently shown to capture quantitatively the relaxation dynamics of a crack depinning from a single obstacle (Chopin et al, 2018).…”
Section: Kinetic Lawmentioning
confidence: 99%
“…The multiple discrete cavitation-dominated cracking process is reminiscent of the discontinuous percolation process of shear transformation zones during the formation of a shear band in MGs (52), the depinning transition of cracks in disordered solids (53), and the stick-slip behavior of frictional instability (54). All these discontinuous processes in disordered systems have the nature of far from equilibrium and perhaps follow at the root of some common physical principles.…”
Section: Discussionmentioning
confidence: 99%
“…From this viewpoint, it is promising to tailor the heterogeneities of glasses to avoid the occurrence of cavitation-induced cracking and thus achieve glasses with sufficient ductility and damage tolerance, such as the recently reported highly ductile amorphous oxide with a dense and flaw-free atomic arrangement (3,5). From a theoretical perspective, the intrinsic heterogeneities of glasses invalidate the classical continuum understanding of dynamic crack propagation (14,15,47,53), which is based on the continuum concept of matter and is valid for the description of generic fracture on the macroscale (4,11). Therefore, further fundamental fracture theory taking into account the heterogeneities of amorphous solids needs to be undertaken to describe the nanoscale cavitation-dominated crack propagation of glasses.…”
Section: Discussionmentioning
confidence: 99%
“…A 5mm thick plate of PMMA is detached from a thick PDMS substrate using the beam cantilever geometry depicted in Fig. 1 [29]. To introduce disorder, we print obstacles of diameter d 0 = 100 µm with a density of 20 % on a commercial transparency that is then bonded to the PMMA plate before bringing it in contact with the PDMS.…”
mentioning
confidence: 99%